The organisation of the preventative and curative medical services and hospital and laboratory systems under a Ministry of Health (London : Co-operative Printing Society)
1919 1919 1910s 18 pages The clinical teachers of the practitioner, the consultants in the hospitals and medical schools, and those practising among the wealthy know but little of, and have failed to protest against industrial and housing conditions, due largely to the exploitation of land, which have led to the most serious deterioration of national health and happiness. The instruction of medical students in preventive medicine is very inadequate. The general practitioner has little opportunity to study or uphold the principles of preventative medicine, and improvements in these directions are urgently necessary. In the matter of diagnosis and treatment of disease, the science of medicine is so vast that no one man can effect what can be done by a group of men, each trained in special lines and provided with adequate equipment. Thus the poor who go to hospital with a medical school often secure a more accurate diagnosis and more skilful treatment than the patients of a private doctor. So much of the practitioner's time is spent on the art of medicine, in visiting, humouring and encouraging his patients, that too little remains for acquiring and practising the science of medicine. Devoted attendance and kindly endeavour cannot compensate for ignorance of the advances of medical science, but they often cloak failure to prevent illness and loss of working capacity, or to save life. A State Service should be under democratic control, both at headquarters and at every local centre. There must be nothing in the scheme to take away the choice of doctor from the patient, but rather to widen and amplify that very restricted choice he now possesses (see Section 11 of Scheme proposed in Part II). It must be the aim of the service to put every discovery of modern medical science, every class of specialist, every comfort of the best type of nursing-home, sanatorium, or hospital, within the reach of all — rich and poor — and not least of all the men and women who are neither one nor the other. The present hospital and panel system must be radically reformed, and the coming Service must not be bureaucratic, but one more resembling the chapters or lodges of a skilled craft. It must not prevent private practice, and no practitioner or patient must be forced to take any part or share in it against his desire. The new system must win on its merits, and be judged with perfect freedom by each individual, who will freely take up his own attitude towards it. The country should be divided into areas of sufficient size to allow of complete medical organisation. The hospital of each area or sub-area should form the head quarters and consultative centre of the unit; its laboratories the home of scientific diagnosis and research. The doctors within the area, and not the single practitioner, would together form the unit. Each medical unit would have control over its own local professional affairs and be linked up to all other units within the area. Together with the local lay Health Committee (see our previous report, "A Ministry of Health"), it would be responsible for the health of the area it served. The staff of the unit would not stay in its headquarters awaiting disease to knock at its doors, but would set about investigating the origins of disease, would teach the laws of healthy living to its community, and would see that healthy conditions were maintained wherever human beings congregate. It would try to ensure that supplies of food were wholesome and adequate, and that adulteration and sophistication were prevented, that weakly individuals were not overworked when ill or requiring relaxation, that infected individuals were not infecting others, and that young infants and children were being reared in a sensible way and on suitable food. In order to carry out this scheme for evolving a healthy people, it will be necessary to inaugurate several activities of the National Health Service, but these must form part of one organic whole, they must necessarily interlap and communicate 2 36/H24/6